Analisis Visual Kostum dan Atribut Sekhmet dalam Komik Marvel - Syaima Antar Morsi; Yully Ambarsih Ekawardhani (ARTic, 2021)
The purpose of this study is to analyze the costume and attributes of Sekhmet's character in one of marvel's comic books titled "The Heroic Age: Prince of Power, where Sekhmet is a female supervillain character that was adapted from Egyptian mythology. In The Heroic Age: Prince of Power, issue 3, Sekhmet is visualized wearing costumes and attributes that match the description and visualization that can be found in ancient Egyptian artifacts. This research used descriptive qualitative with a narrative method and one of Tsukamoto's manga matrix theories, the costume matrix, to analyze further the ornaments and attributes that Sekhmet wore in the comic. This study found that Sekhmet's ornaments and costumes were indeed adapted from Egyptian mythology. However, even with so much similarity, there was an additional costume and attributes that differentiated the visualization of female supervillain Sekhmet and the Egyptian mythology goddess Sekhmet where female supervillain Sekhmet is visualized wearing attributes and costumes specialized for male soldiers, which adds masculinity factor to Sekhmet's female character. Keywords: Egyptian Mythology; Manga Matrix; Marvel; Sekhmet; Visual Analysis